Challenges and conditions for reindeer husbandry in Norway, Sweden and Finland - Holand, Øystein; Hannu, Ulrika; Rasmus, Sirpa; Åhman, Birgitta (Rangifer, 2024)
This report is based on the book "Reindeer Husbandry and Global Environmental Change - pastoralism in Fennoscandia". The book, which was published in 2022, brings together previous and new research compiled within a Nordic collaboration project, ReiGN (Reindeer husbandry in a Globalizing North), funded by NordForsk during the years 2016 – 2021. Grants from NordForsk also funded this report. The report, published in Swedish, Norwegian, Finnish, North Sámi, and English summarizes some of the main results from the book. In nine chapters it describes how reindeer herding is affected by climate change, the continuous loss of reindeer grazing land and other external factors that together represent large challenges for reindeer, reindeer herders and the reindeer herding community as a whole. The report contains perspectives from many different research areas. Each chapter in the report has one or more references and links to chapters in the above mentioned book, which is freely available online (https://doi.org/10.4324/9781003118565). The chapters in the report cover a range of different topics, like present and historical reindeer herding (Chapter 1), the genetic background of the semi-domesticated reindeer (Chapter 2), how reindeer ranges are used and how they are affected by climate change and expanding industrial development (Chapter 3), possibilities for adaptation to a warmer climate (Chapter 4), impact of large predators (Chapter 5), external and internal governance (Chapter 6), reindeer herding as subsistence (Chapter 7), the role of supplementary feeding (Chapter 8), and reindeer health and diseases in a climate perspective (Chapter 9). The report ends with some reflections over the present situation and future perspectives for reindeer herding. The report is aimed at herders and managers, as well as other land users, authorities and policymakers who deal with natural resource management, climate and environmental issues or other matters related to reindeer herding and the use of land and water within the ...